Building the Largest Sample of IR Galaxies. Preliminary Results - Mikayelyan, G. A.; Mickaelian, A. M.; Abrahamyan, H. V.; Paronyan, G. M.
To build the IRAS full extragalactic sample (including both point-like sources - QSOs, and extended ones - galaxies), we have applied several approaches. Cross-correlation of IRAS PSC/FSC Combined Catalogue with optical catalogues of already known galaxies, quasars and blazars such as The NGC 2000.0 Catalog, Third Reference Catalogue of Bright Galaxies, The Roma BZCAT, Astrometric Catalogue 5 and many others. Cross-correlation of IRAS PSC/FSC Combined Catalogue with optical catalogues giving data, which can be used to determine galaxy candidates, for example Sloan Digital Sky Survey (SDSS, contains data about point like and extended objects), The APM North Catalogue (contains data about ellipticity of objects), etc. Cross-correlation of IRAS PSC/FSC Combined Catalogue with GAIA DR3, which gives data about proper motions of objects (we can consider the objects having real proper motions as stars and exclude them from the sample). If all data show the same type of object, then we give it as a genuine one, and if there is an ambiguity, we give the most probable type with a flag. All this will lead to construction of a confident sample of optical counterparts of extragalactic objects of IRAS PSC/FSC: galaxies and quasars. We also will study IR/opt flux ratios, which may serve as one more characteristic to reveal galaxies with very high SFR. We will carry out calculation of IR luminosities for all IR galaxies. We expect revelation of many new ULIRGs and HLIRGs and building their largest samples.
Keywords: Galaxies